Information seeking behaviour of school teachers in rural areas of selected states in Nigeria : a proposed circular model - Kamba, Abdullahi Manir (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2010)
This study investigated the information seeking behaviour of school teachers in rural areas of selected states in Nigeria, a developing country in Africa. The main objectives of the study were to identify the information seeking behaviour of school teachers in rural areas of Nigeria and propose a new model of information seeking behaviour. The study has addressed the questions (i) the information seeking behaviour of school teachers (how they locate and use relevant information for their teaching and leaning), (ii) relationship between demographic factors and information use and seeking pattern of school teachers. Various sources of information utilised by school teachers as well as barriers to information seeking affecting the school teachers were identified and discussed (iii) whether the existing models of information seeking could be applicable, suitable and expandable to study the school teachers' information seeking behaviour. The data was collected using cross-sectional survey design for both quantitative and qualitative data. Stratified sampling with proportionate and random selection was applied to sample the target school teachers in the selected states of Nigeria. The study employed a researcher-developed questionnaire and interview guide using the weaknesses of the existing ISB models and literatures from previous studies. It was preliminarily tested with 84 school teachers, validated by 15 content experts from 7 countries. Findings from the study showed that the information seeking behaviour of school teachers were found to be similar with other respondents else where. However, in this research the findings further showed that the respondents used varieties of ICT to search for information, though they are lacking competent skills. The findings revealed that respondents used the internet and other electronic resources but they hold printed resources as the most preferred resources for their activities. The study also showed that school teachers in rural areas of Nigeria experienced four barriers during the process of information seeking activities which are: environmental, educational, technological and economic/political barriers. The findings of the study revealed that demographic factors of school teachers were found to have significant relationship with library use, information seeking pattern, information use pattern and ICT use. Finally, the research found that, the existing models of information seeking such as Ellis (1989), Kulthau (1994), Wilson (1999), Johnson (1997), Leckie et al (1996), Krikelas (1983) and Al-suqri (2007), might be applicable, suitable and expandable to the study of information seeking behaviour. However, they might not be sufficient enough to be fully utilized in understanding the information seeking behaviour of school teachers, especially in rural areas of Nigeria. In this regards, some modifications, amendments, refinements, and incorporation of other elements have to be made in order to suit the information seeking process of school teachers particularly in rural areas of Nigeria. The study therefore, proposed a new model of information seeking behaviour i.e. circular model framework for school teacher's information seeking behaviour. Recommendations were made to school and library management, government and educational agencies, school teachers and future research.